“El estrés laboral y su influencia psicofísica en el desempeño laboral de los trabajadores del área administrativa del Honorable Gobierno Provincial de Tungurahua”. - Luna Sánchez, Alfredo Javier (2020)
The present research aims to take into account essential aspects related to the physical and psychological health of workers in the administrative area of the Honorable Gobierno Provincial de Tungurahua, the study focused on identifying the causes that led to the different psychological, physical and emotional affectations , which are related to workers, especially those who carry out their activities under the telework modality, this modality had to implement obligatorily by the sanitary emergency caused by the COVID 19 pandemic, the project was carried out through descriptive research allowed to know more about deep down the actual problematic, in particular the symptomatology and the different stress affectations that were traversing the teleworkers; The collection of information and data takes was carried out by means of instruments such as the interview, survey and the Maslach test with its respective method, which allowed to establish real results of the people who suffer some type of stress; The results obtained are manifested through frequent headaches, neck, back and hand pain, sometimes lumbar pains and gastric problems are the most reported. ; concluding that 75% of the staff had symptoms related to the psychosocial stress-burnout factor, originated by telework due to poor organization in distributing activities and even an excess of workload. All this led to the confusion about performance and the role within teleworking.